The value of character education in the Malin Kundang folktale as a tool for social control - Nugraheni, Luthfa; Surachmi, Sri; Salaebing, Muhammad (Universitas Muhammadiyah Malang, 2026)
The weakening of the internalization of character education values in modern society indicates a gap between educational goals and social realities, particularly with respect to parents, social responsibility, and moral awareness. Amid these challenges, folklore as local wisdom has strategic potential to strengthen character formation while functioning as a mechanism of social control. This study aims to identify and describe the character-education values in the Malin Kundang folktale and to analyze its role as an instrument of social control, using a descriptive qualitative approach. Data were obtained from the folktale text and millennial informants (aged 18–35) through a limited literature study and semi-structured interviews, and analyzed using an interactive technique. The findings showed that the Malin Kundang story contained values such as respect for parents, honesty, humility, responsibility, loyalty to identity, and social awareness, which were integrated into a cause-and-effect narrative structure that effectively shaped moral awareness. In addition, the story functioned as a preventive cultural social control mechanism through symbolic moral consequences, such as the curse turning Malin Kundang into stone. Millennials still interpreted the story as a source of life reflection, particularly regarding respect, self-control, and responsibility, indicating that the folktale remains relevant as a medium for character education and social control in contemporary society.